Analysis of switched impedance source/quasi-impedance source DC-DC converters for photovoltaic system - Sapavath Sreenu; Jalla Upendar; Bogimi Sirisha (International Journal of Applied Power Engineering (IJAPE), 2022)
This paper proposes the switched impedance source converter (SZSC) or switched quasi impedance source DC-DC converter (S-qZSC) based photovoltaic (PV) grid-connected systems. To increase the voltage from low level to high level, all PV grid-connected systems need step-up DC-DC converters. This step-up factor can be increased by connecting the terminals of a traditional quasi impedance source DC-DC converter with an additional diode and a switch. In this proposed converter, the capacitor not only serves as a filter. It is, however, bound in series to the charging loops of the inductors. On the one hand, saturated inductors can trigger instability, which can be avoided. When used for dc-ac conversion, however, the modulation index of the backend H-bridge can be set to a wider range. As compared to existing Z-source-based systems, a shorter duty period results in a higher boost factor.